Analisis Pengaruh Migrasi Masuk, Pendidikan dan Upah Minimum Terhadap Kemiskinan di Pulau Sumatera - Nia Diniati; Yusni Maulida; Toti Indrawati (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to understand the influence of In-Migration, Education, and Minimum Wages on Poverty on Sumatra Island. This study uses quantitative methods. The type of data used in this study is secondary data obtained from the Indonesian Central Bureau of Statistics and the Village Community Empowerment Service and the Population and Civil Registration Service of Riau Province. Through the panel data regression method with the Random Effect Model (REM) approach. By using the Eviews Program, the results obtained show that partially, the variables of In-Migration (X1), and Minimum Wages (X3) do not have a significant effect on Poverty on Sumatra Island, while the variable of Education (X2) has a negative and significant effect on poverty on Sumatra Island. Simultaneously the variables of In-Migration (X1), Education (X2), and Minimum Wages (X3) influence poverty on Sumatra Island.With an Adjusted R-squared value of 0.616290, it shows that the variables of In-Migration (X1), Education (X2) and Minimum Wage (X3) influence Poverty on Sumatra Island by 61.6%, while the remaining 38.4% is obtained from variables outside this study.